Shisha Pangma leucogranite, south Tibetan Himalaya: Field relations, geochemistry, age, origin, and emplacement - Searle, M; Parrish, R; Hodges, K; Hurford, A; Ayres, M; Whitehouse, M (1997)
The Shisha Pangma pluton forming most of the Xixabangma (8027 m) massif in south Tibet is one of the 20+ larger leucogranite intrusives that mark the highest structural levels of the Himalayan metamorphic core. The pluton occurs immediately below the Shisha Pangma Detachment, a strand of the South Tibetan Detachment (STD) system, a low angle (30°) north-dipping normal fault placing Paleozoic black slates atop sillimanitc-grade pelites and calc-silicate rocks. K-feldspar augen gneisses containing fibrolite and sillimanite paragneisses along the footwall show strong internal S-C fabrics indicative of down-to-the-north extension. The Shisha Pangma leucogranite is a heterogeneous, polyphase intrusion with an earlier, foliated biotite-rich phase and a later, tourmaline + muscovite rich phase typically containing the assemblage: Kfs + Pl + Qtz + Ms + Tur ± Gt ± Bt ± Sil ± Ap. The highly peraluminous granites have high 87Sr/86Sr ratios (0.738-0.750) typical of pelite-derived anatectites. Nd-depleted mantle model ages (from present Nd isotopic data and an assumed crustal 147Sm/144Nd of 0.10 ± 0.02) are 1.5-2.2 Ga, indicating a substantial early Proterozoic or older crustal residence age for much of the source material. Xenotimes and monazites from a weakly foliated biotite granite immediately beneath the STD (X8) give consistent U-Pb ages of 20.2 ± 0.2 Ma. Zircon, uraninite, and monazite from the main Shisha Pangma tourmaline + muscovite ± garnet phase (X20) give an U-Pb age of 17.3 ± 0.2 Ma. A sill complex above the main leucogranite body is aligned parallel to the metamorphic fabric dipping at 10-30° N, although a few dikes cross-cut the metamorphic fabric beneath the STD. Nowhere do the leucogranites cut the STD, and the age of normal faulting must largely post-date 17.3 ± 0.2 Ma. Muscovite from the main leucogranite phase has an 40Ar/39Ar plateau age of 16.74 ± 0.22 Ma. Apatite fission track ages for leucogranite samples from 5800-8000 m range from 12.3 ± 1.9 to 14.8 ± 0.8 Ma (± 2σ), only slightly younger than the main leucogranite crystallization age. Following crustal melting, steep cooling curves (>90-180°C/myr) and rapid exhumation rates (∼4 mm/yr) from 17-14 Ma resulted in removal of at least 12 km of overburden, both by erosion and normal faulting. If high erosion and exhumation rates correlate with high topography (and high precipitation) these data suggest that the Himalaya reached their maximum topographic elevation around 17 Ma.